Evaluation of stability of the subjects with toe in gait due to increase in femoral head anteversion angle during quiet standing - mohammad Karimi; Keyvan Sharifmoradi; Maziar Sharbafi (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: Toe in gait may be due to metatarsus adductus, increase in tibia torsion and femoral anteversion. It is controversial that it influences on standing stability or not. Therefore, the aim of this study was to evaluate the effects of toe in gait, due to increase in femoral head anteversion, on standing stability. Method: 11 subjects with toe in gait due to increase in femoral head anteversion were recruited in this study. There was also a control group matched with the toe in gait group. A Kistler force plate was used to evaluate stability of the subjects during quiet standing based on center of pressure (COP) sways. Results: The mean values of center of pressure (COP) excursion in anteroposterior direction was 14.41±4.66 and 23.41± 8.17 mm in normal and those with toe in gait, respectively (p-value <0.05). The difference between COP excursion in mediolateral direction in both group was not significant (p-value=0.085). There was a significant difference between velocity and path length of COP in both planes between the groups (p-value<0.05). Conclusion: Based on the results of this study, the subjects with toe in gait due to increase in femoral head anteversion are more unstable in quiet standing than normal subjects.